Effect of consuming lactogenic biscuits formulated with banana (Musa x paradisiaca) flower flour on expressed breast milk (EBM) among lactating working women - Nordin, Z. M.; Abu Bakar, Ibrahim; Omar, Muhammad Nor; Mahmood, Azizah (Rynnye Lyan Resources, 2020)
The most common reasons given for breastfeeding discontinuation among working women is insufficient or low milk supply which related to physiological and psychological factors. In this case, natural galactagogue is suggested as an alternative for lactating women to augment expressed breast milk supply, instead of using drugs as a milk booster. This study investigated the banana flower of Musa x paradisiaca for its galactogenic property on lactating working women. Formulations containing banana flower flour (BFF) and wheat flour with ratio of 50:50 were consumed by randomised lactating working women. A total of 58 mother-infant pairs were assigned to two groups which were placebo group (n=29) who consumed plain biscuits (without addition of BFF) and experimental group (n=29) who consumed prototype biscuits. Expressed breast milk (EBM), anthropometric indices of mothers and infants were recorded before and after the consumption of the biscuits. The result showed that EBM volume after consuming lactogenic biscuits among experimental group was significantly higher compared to placebo groups. The index of mother’s BMI change after the intervention was not statistically significantly different between the two groups (p>0.05). However, the BMI for age index after the intervention was significantly different among the infants (p<0.05), which means that lactogenic biscuit also contributes to the infants' growth status. The usage of banana flower as a galactagogue was useful to help increasing maternal milk production among lactating working women. © 2019 The Authors. Published by Rynnye Lyan Resources.